The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuron.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Updating of Action Selection for Goal-Directed Behavior through the Striatal Direct and Indirect Pathways

Abstract: The basal ganglia play key roles in adaptive behaviors guided by reward and punishment. However, despite accumulating knowledge, few studies have tested how heterogeneous signals in the basal ganglia are organized and coordinated for goal-directed behavior. In this study, we investigated neuronal signals of the direct and indirect pathways of the basal ganglia as rats performed a lever push/pull task for a probabilistic reward. In the dorsomedial striatum, we found that optogenetically and electrophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
161
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(186 citation statements)
references
References 89 publications
16
161
2
Order By: Relevance
“…Our findings are also compatible with computational accounts that predict that lowering tonic dopamine, which facilitates iSPN activity and suppresses dSPN activity (59,60), shifts explore/exploit balance towards exploration (61,62). Finally, if behavioral switching is viewed as exploring action space, our iSPN data may relate to recent studies that report iSPN activity increases in response to outcomes preceding switch trials (25,64).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are also compatible with computational accounts that predict that lowering tonic dopamine, which facilitates iSPN activity and suppresses dSPN activity (59,60), shifts explore/exploit balance towards exploration (61,62). Finally, if behavioral switching is viewed as exploring action space, our iSPN data may relate to recent studies that report iSPN activity increases in response to outcomes preceding switch trials (25,64).…”
Section: Discussionsupporting
confidence: 89%
“…The DMS is primarily composed of D1 receptor expressing dSPNs and D2 receptor expressing iSPNs (20), whose activity reflect task features including movement, cues, and value (16,(21)(22)(23)(24)(25)(26). Consistent with predictions from functional neuroanatomy (27)(28)(29) and theoretical work (30,31), optogenetic stimulation of dSPNs promotes movement and reinforces actions ('go' functions) (32)(33)(34) whereas optogenetic stimulation of iSPNs inhibits movement and drives aversion ('no go' functions) (32)(33)(34).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although we found no significant effect on either of these factors alone, the overall impairment by rats with iSPN inhibition appears to be due to their combination. Indeed, there is recent evidence to suggest that both of these forms of response flexibility require iSPNs; Matamales et al (2020) demonstrated that ablating iSPNs in the DMS encourages recurrent responding during the extinction of goal-directed learning (response perseveration), and Nonomura et al (2018) have shown that iSPNs in the DMS encode non-rewarded responses, and, if optogenetically stimulated following a non-rewarded response, promote switching to an alternate response.…”
Section: Spns and Goal-directed Updating: A Role For The Indirect Patmentioning
confidence: 99%
“…A significant body of experimental work has established that corticostriatal synapses represent one site of such plasticity, which is triggered when a behavior followed by an unexpected reward leads to a change in dopamine levels [8,39,44]. Because the corticostriatal synapses represent a key input pathway to the cortico-basal ganglia-thalamic (CBGT) circuits, these dopaminergic changes have been shown to have a critical impact on global network computations related to action selection [2,7,12,15,24,37,51].…”
mentioning
confidence: 99%